Impact of the stellar oblation effect on estimation of the magnetic dipole strength - Khalack, V. (Кинематика и физика небесных тел, 2005)
The surface magnetic field structure of an ellipsoidal star is modelled in the frame of the magnetic charge description (MCD) approach. It is shown that the stellar oblation effect can lead to the essential overestimation of the magnetic dipole strength value obtained from the mean crossover effect (up to 12%) and quadratic magnetic field (up to 8%) in comparison with its theoretical value obtained for the case of the spherically symmetric star. Taking into account the gravity-darkening phenomenon is argued that this overestimation increases with the growth of the effective gravity difference at the equator and poles of the star. The data of the mean longitudinal magnetic field provide the most correct estimation of the magnetic dipole strength value in the ellipsoidal star.